(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The combination of reporting and their information requests is considered. The sphere of influence and interest’s conflict between the participants of corporations are established. Satisfying the information needs and material interests of each consumer is difficult and hopeless. The information needs of owners, investors as the main stakeholder of accounting and reporting information are determined. Most stakeholders (inc. founders, shareholders and other owners) are most interested in information on two areas of enterprises and corporations activity: profitability and financial stability. The information about profitability allows owners, investors, shareholders to expect on dividends receiving, stable financial position – to build strategic plans for the future, to plan systemic and non-system risks. The reporting information features in the context of corporate management and related corporate accounting and corporate reporting definitions are investigated. Proposals for expanding the investment component of corporate reporting by introducing additional financial and non-financial information are given. Ways of increasing the informing of enterprises and corporations owners are offered. The distinctive features of goodwill arising from the purchase and consolidation, the method of their accounting and reporting are established. The methods of profit and cumulative income reflection in the consolidated statements when an uncontrollable share is present in the corporation are generalized. The statements extension by introducing additional non-financial information about the structure of management and control of corporations is proposed. It is necessary to expand information about economic relations within the corporation in the integrated reporting forms, integration of indicators in consolidated financial statements. Extended information for submitted in the newly introduced Management Report is proposed.